AHWAL AT-TASAWWUF (BUAH TASAWUF) - Miswar Miswar (Universitas Islam Negeri Sumatera Utara Medan, 2017)
Understanding Sufism in plenary is absolute for anyone who wants to make Sufism a way of life. A complete understanding of Sufism makes itself to the ultimate goal. Conversely partial understanding will only make yourself to stray away from the goal. Ahwal at-tasawwuf or the fruit of tasawuf is a part of Sufism that absolutely must be understood in the plenary. Sufism consists of mahabbah, kasyf, inspiration and sacred. There is a phenomenon among admirers of the path of Sufism that makes it a goal. Some evens want to grab it for curiosity, or evens for the sake of popularity in the eyes of humans. It is an intention that is not based on the true science of ahwal at-tasawwuf. Ahwal at-tasawwuf should be understood as it should, not as a purpose that turns away from God. This paper will explain what and how to understand ahwal at-tasawwuf.